Biochemical and Physiological Changes in Rice Plants Due to the Application of Herbicides1 - LANGARO,A.C. (2016)
ABSTRACT The application of herbicides, even if selective, can cause biochemical and physiological changes, resulting in oxidative stress. This stress comes from the accumulation of reactive oxygen species produced due to exposure to the herbicide. However, plants have developed defense strategies, which can be enzymatic or non-enzymatic. The objective of this study was to evaluate the morphological and metabolic changes such as photosynthetic parameters, oxidative damage and antioxidant enzyme activity of rice plants after applying herbicides. For this, a study was conducted in a greenhouse and laboratory and the treatments consisted of application of imazapic + imazapyr, quinclorac, bentazon, cyhalofop-butyl, penoxsulan, bispyribac-sodium and carfentrazone-ethyl, in addition to control without herbicide. The phytotoxicity in plants was strong and there was a reduction in photosynthesis, stomatal conductance and efficiency of water use in plants treated with carfentrazone-ethyl. Furthermore, the application of carfentrazone-ethyl resulted in lower chlorophylls and carotenoids and increased lipid peroxidation and proline accumulation. Changes in the activity of enzymes belonging to the antioxidant system were inspected by applying herbicides. The application of herbicide alters the physiology of rice plants, triggering responses to oxidative stress, which are more pronounced when used carfentrazone-ethyl.